ANALISIS CURAH HUJAN DAN KLASIFIKASI TIPE IKLIM MENGGUNAKAN METODE SCHMIDT-FERGUSON (STUDI KASUS: DANAU TEMPE) - Wahyuni; Vinsensia Paola Prattyni; Hasanuddin; Kalangi, Hendry Tanoto; Leonard, Franita (Jurnal Media Teknik Sipil, 2024)
ABSTRACT Climate change has a very significant impact on the human life cycle and is one of the important contents of the global environment that requires great attention to mitigate climate change. This study aims to identify climate types based on the Schmidt-Ferguson classification. The research method used is the survey method and literature review. This study uses secondary data in the form of rainfall, air humidity, air temperature, and wind direction and speed. From this study, the results obtained are based on climate classification with the Schmidt-Ferguson method. The results of the study on the classification of the climate type of Lake Tempe have a Climate type A which is included in the area with tropical rainforest vegetation with a very wet climate. This is in line with the conditions of the agricultural plantation sector around the research location, where most of the area is fertile and overgrown with secondary crops. With the classification of rainforest vegetation with a wet climate, high rainfall has an effect on humidity to be high, temperatures to be low, and the dominant wind direction moves to the southwest. Keywords: climate classification, Schmidt - Ferguson, rainfall